Post Transplant Health Related Quality of Life (HRQL) Among Kidney Transplantation Recipients in Nepal - Adhikari, Ashok; Subedi, Samjhana; Giri, Mahendra; Maharjan, Prabindra; Chaulagain, Aayush (NPRC Journal of Multidisciplinary Research, 2026)
Background: End Stage Renal Disease (ESRD) is a growing public health concern, especially in low resource countries like Nepal, where access to renal replacement therapy is limited and costly. Kidney transplantation (KT) is the most effective and cost-efficient treatment, yet little is known about recipients’ quality of life in the Nepali context. This study assessed health related quality of life (HRQOL) among kidney transplant recipients (KTRs) and explored associated factors.Methods: A hospital based cross sectional study was conducted among 183 KTRs attending follow up at KIST Teaching Hospital between December 2025 and February 2026. Participants ≥18 years and at least six months post-transplant were included. Data were collected using a structured questionnaire and the standardized KTQoL instrument. HRQOL scores were analyzed using descriptive statistics and chi-square tests (p < 0.05).Results: Most of the participants were male (70.5%), and two thirds were aged 31 - 45 years. Nearly three quarters rated their post-transplant health as good or very good, and most reported improved daily activities (78.7%) and breathing (73.2%). Despite these improvements, about one third experienced anxiety or worry about infection and graft survival, and more than half (58.5%) reported financial strain due to lifelong immunosuppressive therapy. Higher HRQOL was associated with younger age, higher income, longer post-transplant duration, and good medication adherence, while financial hardship was linked to lower HRQOL.Conclusion: Kidney transplantation in Nepal noticeably improves physical functioning and overall health perception. However, psychological stress and economic challenges persist. Strengthening psychosocial support, promoting adherence, and expanding financial protection are crucial to optimize long term HRQOL outcomes.